Antipsychotics promote GABAergic interneuron genesis in the adult rat brain: Role of heat-shock protein production. (September 2017) - Kaneta, Hiroo; Ukai, Wataru; Tsujino, Hanako; Furuse, Kengo; Kigawa, Yoshiyasu; Tayama, Masaya; Ishii, Takao; Hashimoto, Eri; Kawanishi, Chiaki
Abstract: Current antipsychotics reduce positive symptoms and reverse negative symptoms in conjunction with cognitive behavioral issues with the goal of restoring impaired occupational and social functioning. However, limited information is available on their influence on gliogenesis or their neurogenic properties in adult schizophrenia brains, particularly on GABAergic interneuron production. In the present study, we used young adult subventricular zone (SVZ)-derived progenitor cells expressing proteoglycan NG2 cultures to examine the oligodendrocyte and GABAergic interneuron genesis effects of several kinds of antipsychotics on changes in differentiation function induced by exposure to the NMDA receptor antagonist MK-801. We herein demonstrated that antipsychotics promoted or restored changes in the oligodendrocyte/GABAergic interneuron differentiation functions of NG2(+) cells induced by the exposure to MK-801, which was considered to be one of the drug-induced schizophrenia model. We also demonstrated that antipsychotics restored heat-shock protein (HSP) production in NG2(+) cells with differentiation impairment. The antipsychotics olanzapine, aripiprazole, and blonanserin, but not haloperidol increased HSP90 levels, which were reduced by the exposure to MK-801. Our results showed that antipsychotics, particularly those recently synthesized, exerted similar GABAergic interneuron genesis effects on NG2(+) neuronal/glial progenitor cells in the adult rat brain by increasing cellular HSP production, and also suggest that HSP90 may play a crucial role in the pathophysiology of schizophrenia and is a key target for next drug development.